Increasing to precision spectral device checking the technological processes of communition - Корнієнко, В. І.; Гусєв, О. Ю. (Problems of Informatization and Control, 2009)
The Designed algorithm of the processing signal, providing increasing to precision in spectral device of the checking the technological processes of communition by improvements to their selectivity and reductions to instrumental error. Evaluated efficiency and expenseses on realization of this algorithm